FOOD THERAPY AND EDUCATION NEXUS AGRONOMIC FRAMEWORK. EVIDENCE FROM MOUNTAIN BERRIES - R. Brejea; M. Covaci; B. Covaci; C. Selma (Harčova Nauka ì Tehnologìâ)
Background: Berries from mountainous regions, essential members of the Plantae kingdom, play a vital role in the present health and medical context during the ongoing pandemic, particularly in establishing the framework for natural therapy. Researchers have extensively investigated berry-derived extracts to evaluate their potential in inhibiting infectious diseases. The authors delved into specialized literature, formulating agronomic engineering strategies aimed at augmenting the behavior consumption of mountain berries. Methods: In this study, the authors delve into nutritional information, encompassing calories, fats, carbohydrates, fibres, and proteins, comparing values for regular berries (based on USDA values) and mountain berries (derived from their own research). The investigation reveals that mountain berries boast superior nutritional values, emphasizing their potential health benefits over standard berries as per USDA guidelines. Results: Berries sourced from mountainous regions, including Hippophae rhamnoides (sea buckthorn) from the Elaeagnaceae family, Vaccinium vitis-idaea (blueberry) from the Ericaceae family, Ribes uva-crispa (gooseberries), and Ribes nigrum (currants) from the Grossulariaceae family, as well as Aronia melanocarpa (chokeberry), Rubus fruticosus Rosales: Rosaceae (European blackberry), and Rubus idaeus (raspberry) from the Rosaceae family, play a pivotal role in both preventing and combatting various infectious diseases. Conclusion: This manuscript succinctly underscores the significance of specific mountain plants aligning with the attributes of biologically produced products to fortify health-promoting behaviors. The research findings underscore that mountain berries exhibit qualitative values that surpass standard berries, as outlined by the USDA.